Nanoparticle-Based Drug Delivery Systems: A Promising Approach for Targeted Ulcerative Colitis Therapy - Tanwar, Neha; Kaur, Loveleen; Chopra, Hitesh (Scripta Medica, 2025)
Inflammatory bowel disease (IBD), includes ulcerative colitis (UC) and Crohn’s disease (CD), is characterised by recurrent, chronic inflammation of the gastrointestinal system. For the treatment of UC, oral medication delivery to the colon is largely favoured since it increases their effectiveness while lowering systemic toxicity. To deliver oral a medication to the colon, which is at the distal end of the gastrointestinal system is however challenging, because of physiological difficulties, biochemical barriers and environmental obstacles, such as those brought on by mucus and epithelium. Recent preclinical studies have suggested that targeted medication administration to the colon using nanoparticle-based drug delivery systems (DDS) may be a promising strategy for the treatment of UC. Additionally, this study offers a thorough assessment of newly discovered naturally produced nanoparticles (such as extracellular vesicles and plant-derived nanoparticles) as well as DDS based on synthetic nanoparticles. These innovative UC treatment plans based on nanoparticles may present a chance for the clinical application of nanoparticle formulae.